Which Combination of Impossible Trinity Choices Ensures Output and Price Stabilities in India? A Sign‐Restricted Vector Autoregressive Analysis. Issue 3 (23rd September 2022) - Arora, Nitin; Malik, Deepika; Arora, Rahul
Abstract : India has faced the impossible trinity challenge after it opened up its capital account post‐1990s reforms. Accordingly, simultaneous achievement of three macroeconomic objectives, namely exchange Rate Stability, capital openness and monetary independence, is an impossible task and any combination of two objectives can be achieved by losing the third one. This attempt, therefore, validates the existence of impossible trinity in India and investigates its impact on the stability of both, economic growth and prices. The sign‐restricted vector autoregressive (VAR) methodology has been used to confirm the existence of impossible trinity and to identify the best trilemma policy combination for the Indian economy in order to achieve stable output growth with steady prices. A trinity combination of "capital openness" and "exchange rate stability" is found to be the best in achieving stability of macroeconomic indicators under evaluation. Furthermore, the absence of trinity in India is inferred to ensure macroeconomic stability. However, maintaining its absence for a substantial period is noticed to be a near‐impossible task.